2018
DOI: 10.1093/ptj/pzy045
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Blended Physical Therapist Intervention in People With Hip Osteoarthritis, Knee Osteoarthritis, or Both: A Cluster-Randomized Controlled Trial

Abstract: BackgroundIntegrating physical therapy sessions and an online application (e-Exercise) might support people with hip osteoarthritis (OA), knee OA, or both (hip/knee OA) in taking an active role in the management of their chronic condition and may reduce the number of physical therapy sessions.ObjectiveThe objective of this study was to investigate the short- and long-term effectiveness of e-Exercise compared to usual physical therapy in people with hip/knee OA.DesignThe design was a prospective, single-blind, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
152
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(163 citation statements)
references
References 38 publications
4
152
0
7
Order By: Relevance
“…First, national and international clinical LBP guidelines were studied. Second, the results and experiences from the previous study on e-Exercise Osteoarthritis were used [21][22][23].…”
Section: Steps 1 and 2 Contextual Inquiry And Value Specificationmentioning
confidence: 99%
See 2 more Smart Citations
“…First, national and international clinical LBP guidelines were studied. Second, the results and experiences from the previous study on e-Exercise Osteoarthritis were used [21][22][23].…”
Section: Steps 1 and 2 Contextual Inquiry And Value Specificationmentioning
confidence: 99%
“…If patients were insufficiently physically active, the physiotherapist could activate the graded activity functionality and set a goal to reach within 12 weeks. This graded activity functionality with tailored feedback has been studied previously in two osteoarthritis studies [23,35]. Patients received weekly reminders to visit the web application.…”
Section: E-exercise Lbp Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…At the long-term, e-Exercise LBP could result in an improved handling of recurrent LBP and direct and indirect costs. This blended care intervention is an adapted version of previously developed and evaluated blended physiotherapy programs [34,35]. A pilot study using a prototype of the e-Exercise LBP intervention in 41 patients with LBP demonstrated feasibility and proofof-concept on functional disability and pain [33].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…Primary care physiotherapy practices will be invited by letter to participate in the study. Contact details of potential participating practices will be obtained from the professional network of the authors and a previous e-Exercise study [35]. Additionally, a recruitment advertisement will be placed in the online newsletter of The Royal Dutch Association for Physiotherapy (KNGF).…”
Section: Primary Care Physiotherapy Practicesmentioning
confidence: 99%